Packing the cartesian product of two complete graphs with hexagons - Fu, Hung-Lin; Huang, Ming-Hway (Utilitas Mathematica, 2005)
In this paper, we completely solve the problem of finding a maximum packing of Km × Kn, the cartesian product of two complete graphs with edge-disjoint 6-cycles, and minimum leaves are explicitly given. Subsequently, we also find a minimum covering of Km × K n.